Review on Systematic of Calanoid Copepod (Crustacea) from Seagrass and Coral Areas of the East Coast of the Malay Peninsula - Baba @ Abdul Kadir, Mohd Afandy (2002)
A study has been carried out on the systematic of calanoid copepod from samples taken off sea grass and coral area in East Coast of Peninsular Malaysia. The material examined was taken from various samples collected since 1990 until 1997 in Pulau Sibu, Pulau Besar, Pulau Redang and Pulau Bidong. Thirty-four species representing 16 genera and 12 families were described and illustrated. Six species are new record for Malaysian coastal water. They are Subeucalanus crassus, S. subcrassus, S. pileatus, Labidocera kroeyeri, Centro pages yamadai and Bestiolina similis. Subeucalanus is a new record for genus. This study also found that the species Centropages yamadai is also new to Indo Pacific region. This study also reviewed the systematic and distribution of calanoid copepod in Malaysian waters based on published and unpublished literatures. Misidentification and misuse of species names in the literature have been corrected where possible.